FOREIGN DIRECT INVESTMENT IN LATIN AMERICA: THE CASE OF PERU - METAXAS, Theodore; KECHAGIA, Polyxeni (Theoretical and Practical Research in Economic Fields; Vol 7 No 2 (2016): TPREF, Volume VII, Issue 2(14), Winter 2016, 2016)
The majority of the Latin American countries proceeded to political, financial and social reforms so as to improve their attractiveness and to absorb more foreign capitals in order to achieve economic growth. Among the developing countries of the region, Peru managed to attract significant amounts of foreign direct investment mostly because of the abundance of natural resources. Nevertheless, Peru did not manage to become the top foreign capitals destination among the Latin American countries for several reasons. It is observed that the foreign investors’ dominant policy in FDI, the fact that the majority of the infrastructure realized in urban regions, the investment conditions, the external debt, the private sector and the ineffective use of natural resources held back the country’s attractiveness to foreign investors.